Assessment the Output of National Provisions Restricting the Acquisition of Agricultural Land After EU Accession of Bulgaria - Kopeva, Diana (Research Papers, 2012)
During the accession negotiations, Bulgaria requested the possibility to maintain existing national provisions restricting the acquisition of agricultural land or forests for seven years. The motivation considered these derogations necessary, in order to preserve the socio-economic agricultural structure of the countries from shocks that might arise from the differences in land prices and income with the rest of the European Union, and to be able to pursue an effective agricultural policy. The study analyses the results of negotiated derogations four years after EU accession; identifies factors having influence over the outputs of national provisions restricting acquisition of land/forests by foreigners. The fact that Bulgaria is not the only country with such derogations, make possible comparative analysis of results achieved with those in countries from first wave (Poland, Czech Republic, Romania, Estonia, Latvia, Lithuania, Hungary, Poland and Slovakia). Agriculture development in Bulgaria in the last four years, shows that although existing restrictions, differences between Bulgaria and EU-25 definitely decreased over time. Bulgaria has to take advantage of the rest of the period to stimulate development of agriculture and to prepare for 2014 when all restricting provisions will be abolished.